Promoting students' speaking spontaneity through games - Diyah Rofa Abdulah (Journal of Applied Linguistics (ALTICS), 2019)
This paper reports on speaking spontaneity. Having ability to speak spontaneously is a plus point and measuring the success of students to get high grades in the schools. Unfortunately, not everyone can speak spontaneously. Promoting students’ speaking spontaneity through games in teaching academic English speaking to students who are learning english as a foreign language in a junior high school, West Java, Indonesia is very important. The objective of this research is to find out what games that teacher used to promote students’ speaking spontaneity and to know the students’ responses through the implemented games. This research was conducted qualitatively by employing the method of descriptive research. The study was conducted towards students in IX graders at a Junior High School of Tasikmalaya. The researcher collected the data by using observation and questionnaire. From the research findings, it can be concluded that the teacher used five games, such as Bingo Game, Stars Game, Dorr Game, Jumping Game, and Line Game to promote students’ speaking spontaneity and the students’ response towards the implemented game chose the Stars Game as the most interested game among the others because of the use of realia such as stars in learning process.